Development System and Reconstruction Method of Translation-Rotation Computed Tomography Using Efficient Sampling - Nuril Ukhrowiyah; Khusnul Ain (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2011)
Translation-rotation computed tomography system has been successfully built on this research. The system can be used for the scanning process with sampling method square and hexagonal. It also has been obtained interpolation and reconstruction methods are able to produce reconstruction images fast and accurate. Translation-rotation computed tomography system was built by assembling several instruments that have been made and have existed in the laboratory. Performance of the system was tested by scanning test object. Scanning process has been conducted with the circular test object from metal. Scanning process carried out by performing various of three resolutions, i.e. 31 pixels × 31 pixels, 63 pixels × 63 pixels and 127 pixels × 127 pixels. The sinogram data are square and hexagonal patterns. The sinograms are reconstructed by SCFBP (Summation Convolution Filtered Back Projection) and ART (Algebraic Reconstruction Technique) reconstruction method. Hexagonal sinogram pattern has been interpolated by vertical, horizontal and cross interpolation before reconstructed by ART and SCFBP reconstruction method. Reconstruction image of hexagonal pattern were analyzed by comparing the line profile and its rmsd value of the reconstruction image of square pattern. Performance of the constructed system in the research produced reconstruction image appropriated with objects test. The best interpolation for hexagonal sinogram pattern is cross interpolation. The ART methods produced image reconstruction better than SCFBP reconstruction methods.